213 from Conception to Birth: The Role of Minerals on Beef Cattle Fetal Programming. (21st September 2022) - Diniz, Wellison; Menezes, Ana Clara Baião; McCarthy, Kacie L; Hall, Jean; Caton, Joel S; Dahlen, Carl R; Ward, Alison K
Abstract: Fetal adaptations to nutrition in utero lead to long-term effects on fetal growth and postnatal performance. Although required in minute amounts, minerals play an essential role in fetal programming, likely through epigenetic mechanisms. Thus, changes in the embryonic and fetal epigenome modulate gene transcription and, consequently, the differentiation, growth, and development of cells and tissues. Despite the growing knowledge in nutritional epigenetics and gene expression, literature on the implications of minerals on the (epi)genome and fetal development is still scarce. Our research investigates fetal and postnatal offspring outcomes in response to maternal nutrition throughout the periconceptual period of pregnancy using a beef cattle model. We have reported placental adaptations through changes in gene expression in beef heifers supplemented with vitamins and minerals (113 gheifer-1d-1) during the first 83 days of pregnancy. We found coordinated crosstalk between fetal-maternal tissues and a fine-tuned regulation of placental genes involved with nutrient transport, tissue function and differentiation. Interestingly, the concentrations of minerals and amino acids in the allantoic and amniotic fluids and maternal serum were also affected. Furthermore, genes were differentially expressed in the fetal brain, liver, and muscle in response to the maternal diet. The nutrient-sensing PI3K-Akt signaling pathway was over-represented in muscle and cerebrum, whereas mineral and lipid metabolism were identified in the liver. A second study showed that providing supranutritional maternal selenium supplementation (105 mg of Se/wk as Se yeast) during different trimesters of gestation increased Se concentration in the whole blood and muscle of newborn calves. Likewise, calves born to dams supplemented in the last trimester had increased expression of myogenic genes. Altogether, these findings reinforce the implications of maternal nutrition during pregnancy on fetal programming. However, further studies are still required to understand the regulatory mechanisms and postnatal effects.